Delivery of Insulin via Skin Route for the Management of Diabetes Mellitus: Approaches for Breaching the Obstacles - Abdul Ahad; Mohammad Raish; Yousef A. Bin Jardan; Abdullah M. Al-Mohizea; Fahad I. Al-Jenoobi (MDPI AG, 2021)
Insulin is used for the treatment of diabetes mellitus, which is characterized by hyperglycemia. Subcutaneous injections are the standard mode of delivery for insulin therapy; however, this procedure is very often invasive, which hinders patient compliance, particularly for individuals requiring insulin doses four times a day. Furthermore, cases have been reported of sudden hypoglycemia occurrences following multidose insulin injections. Such an invasive and intensive approach motivates the quest for alternative, more user-friendly insulin administration approaches. For example, transdermal delivery has numerous advantages, such as prolonged drug release, low variability in the drug plasma level, and improved patient compliance. In this paper, the authors summarize different approaches used in transdermal insulin delivery, including microneedles, chemical permeation enhancers, sonophoresis, patches, electroporation, iontophoresis, vesicular formulations, microemulsions, nanoparticles, and microdermabrasion. Transdermal systems for insulin delivery are still being widely researched. The conclusions presented in this paper are extracted from the literature, notably, that the transdermal route could effectively and reliably deliver insulin into the circulatory system. Consistent progress in this area will ensure that some of the aforementioned transdermal insulin delivery systems will be introduced in clinical practice and commercially available in the near future.